Apport De La Prospection Géoelectrique (Tomographie Et Trainé Éléctrique) À L’étude Des Tourmalinites Stanniferes d’Achmmache (Maroc Central) - Azizi, Moussaid; Mohamed, Aissa; Hafid, Mezougane; Abdel-Ali, Kharis; Driss, Hritta; Mustapha, Boualoul (European Scientific Journal, ESJ, 2018)
The Achemmache region is located in the East of El Hammam district, in the Eastern part of the Northern Hercynian Central Morocco; Tin concentrations, economically exploitable, have been recognized in brecciated tourmaline structures of Late Visean, and generally oriented E-W. Therefore, they contrast with other tourmaline oriented NE-SW which proved barren. In order to keep the horizontal and vertical continuity as well as the dip and extension of mineralized structures in the sector, a geophysical survey by Horizontal Electrical resistivity (TE) prospecting and Electrical Tomography was performed in the region. The TE1 profile was performed in the West Zone where the mineralized structures outcrop; it allows highlighting four positive anomalies, while the TE2 profile was carried out in Eastern zone of the sector where the mineralized structures are largely hidden. It can also bring out only two rather distant positive anomalies. These anomalies correspond to mineralized structures of tourmaline. While a duplicate executing of TE1 and TE2, mineralized structures show that some resistant ones have different dips, while some others are subvertical. The TM1 profile was carried out at the same location of electrical TE1 profile in order to confirm the tourmaline structures. The TM1 shows from the NW to the SE an alternation of resistant levels with the relatively conductive levels. The resistive levels are correlated with tourmaline structures identified by the horizontal electrical resistivity. The structures dips show a good correlation between the electrical tomography results and these obtained by the horizontal electrical resistivity profiles with duplicate mode. The study of thin sections and polished sections of the SCA110 and SCA8 core drilling, carried out by BRPM, allowed to recognize, at the mineralized zones, a paragenesis composed of gangue minerals such as quartz, calcite, tourmaline metallic minerals, sulphides and oxides such as magnetite and cassiterite.